THE EXISTENCE OF CLEMENCY FROM A CRIMINAL LAW PERSPECTIVE - Olpiyanti SS , SH, MH, C.Me, Lilis (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The Republic of Indonesia is a country based on on law . The 1945 Constitution stipulates that the Republic of Indonesia is a rule of law ( rechstsaat ) proven from provision in Opening , Trunk Body , and Explanation 1945 Constitution . In countries with level diversity its vast population like Indonesia, system presidential This effective For ensure system strong and effective government .​ However often , because strong the authority he has , arises problem regarding with dynamics democracy [1]. Therefore​ that , deep change 1945 Constitution . Concerning authority president give pardon , called authority judicial president , or​ also called as power president with consultation . Power with consultation is deep power​ its implementation need proposal or advice from related institutions​ with material power That's pardon, isn't it ? is effort law . Although clemency can change the status of the penalty someone , pardon looked at as right its only prerogative is in hand President . Legal effort only those mentioned in the Criminal Procedure Code. After paying attention, the regulations regarding pardon, namely Law Number 22 of 2002, are deemed to need to be improved . The law does not clearly regulate the maximum time limit for applying for clemency. The pardon law only states that a second pardon can be applied for two years after the first pardon. Pardon can also be applied for by the convict or his family. So if pardon from a death row inmate is rejected, the family can apply for it again and this can be done twice each time. This kind of situation takes a very long time, and can delay the execution of death row inmates.